Complicated enteric fever: a case series - Shrivas, Vijay Kumar; Rai, Manoj Kumar; Chandel, Sandhya (International Journal of Advances in Medicine, 2020)
Enteric fever is endemic in Indian subcontinent. Authors are presenting 3 rare cases of complicated enteric fever. The first case is a case of enteric fever which was complicated by ARDS leading to respiratory failure. The second case is a case of enteric fever which was complicated by severe thrombocytopenia and the third case is a case of enteric fever which was complicated by severe encephalopathy. In this study authors have discussed and compared the similar cases found in India and other parts of the world. The physicians who are taking care of the patients of enteric fever should be aware of the above complications.